Simulation approach for optimal design of vacuum cooling on broccoli by simulated annealing technique - Tian, Ding; Alves, W. A. L.; Araújo, S. A.; Santana, J. C. C.; Jiangang, Ling; Jianchu, Chen; Donghong, Liu (International Journal of Agricultural and Biological Engineering, 2014)
Water-spraying is regarded as an effective method to reduce the weight loss of product during vacuum cooling process. This study aimed to investigate the effect of vacuum cooling factors on the weight loss of postharvest broccoli, and attempted to optimize the treatment conditions by simulated annealing (SA) technique. An algorithm based on simulated annealing meta-heuristic technique was developed to identify the optimum condition for vacuum cooling treatment of broccoli. Results demonstrated that the SA algorithm could adjust well with the simulation of the broccoli cooling process. The best condition was at 200 Pa of pressure, 274 g broccoli, 6% of water volume and 40 min processing time. Under this condition, a product with only 0.35% of weight loss and 1.48°C final temperature was obtained. The developed method may help to effectively control the weight loss during vacuum cooling process and reducing the economic loss.Keywords: broccoli, vacuum cooling, simulated annealing, optimizationDOI: 10.3965/j.ijabe.20140705.012Citation: Ding T, Alves W A L, Araújo S A, Santana J C C, Ling J G, Chen J C, Liu D H. Simulation approach for optimal design of vacuum cooling on broccoli by simulated annealing technique. Int J Agric & Biol Eng, 2014; 7(5): 111－115.